Bunga Bank Perspektif DSN-MUI dan Fatwa Majelis Tarjih dan Tajdid Muhammadiyah - Kamto, Kamto (Kosmik Hukum, 2022)
The prohibition of bank interest has been widely discussed in recent times and is also the conclusion of various conferences, scientific seminars, and decisions in several fields, including research institutes in various parts of the Islamic and non-Islamic world. With this prohibition, Allah certainly prepares other things in the form of halal as a replacement. So it is certain that behind the prohibition there are other things that are given by Allah as substitutes that are lawful and good. This is a general rule without exceptions. This study aims to find out what bank interest is and what the law is from the perspective of MUI fatwa and Muhammadiyah fatwa. This type of research is library research with a normative approach and is supported by primary and secondary data in its review. This research provides an answer that in the MUI fatwa what is called bank interest is money interest, so any form in the name of interest whether carried out by institutions, banks, insurance, capital markets, pawnshops, cooperatives or other institutions and or carried out by individuals is called usury and the law is unclean. According to the Muhammadiyah fatwa, what is called riba means addition to the principal capital lent and this addition is binding and agreed upon. However, when what happens is not binding and is not agreed upon, it is not called usury. Unfortunately, the Muhammadiyah Fatwa does not explicitly mention the law of usury, but only recommends dealing with sharia principles. Â Keywords: Media, in Sharia Banking Disputes, in the Religious Courts